APPLICATION OF INTERPERSONAL COMMUNICATION SKILLS IN ELEMENTARY SCHOOL CHILDREN THROUGH COUNSELING GUIDANCE - Yuris, Evicenna (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to explore and analyze the application of interpersonal communication for elementary school children through Guidance Counseling. This research uses a qualitative approach with the method used is literature review. The subjects in this research were elementary school children. The research results reveal that interpersonal communication is very necessary to build good character, to get to know other individuals with different characteristics. This introduction is important for individuals in respecting other individuals and also in providing advice. The process of giving advice is in guidance counseling. With counseling guidance, children can understand and accept themselves and their environment, and can direct themselves to achieve better self-adjustment. Seeing that children spend a lot of their day at school, the role of teachers in building good interpersonal communication through counseling for elementary school children is really needed.